NARKOTIKA JENIS KATINON DALAM PERSPEKTIF ASAS LEGALITAS - Ayu Lestari, Komang; Surya Darmajaya, Ida Bagus (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 04, Juni 2013, 2013)
Now the rampant drug abuse by young people. Narcotics also continues to grow more and more varied types. Example in Case of Raffi Ahmad, National Narcotics Agency discovered the new type of narcotics named cathinone. Narcotics of this type have not been regulated The Act Number 35 Year 2009 regarding Narcotics, as referred to the legality principle so that the cathinone substance’s user can not be able to be punished.
Keywords: narcotics, cathinone, legality